Implementasi Projek Penguatan Profil Pelajar Pancasila Sebagai Upaya Menumbuhkan Jiwa Kewirausahaan - Putri Ayu Anisatus Shalikha (Jurnal Pendidikan Ekonomi, 2022)
In today's uncertain times, fostering an entrepreneurial spirit through co-curricular learning activities for high school students as a provision to be able to live independently is very necessary. Learning loss and the decrease in students' motivation to carry out learning offline is the impact of distance learning. Schools through the implementation of the Independent Curriculum design learning activities in the form of projects to strengthen the profile of Pancasila students. The main purpose of this research is to reveal how schools can inspire students' entrepreneurial spirit through a project to strengthen the Pancasila student profile. This research is a case study at the high school level in Probolinggo City which was used as a pilot project for implementing an independent curriculum by the Ministry of Education, Culture, Research and Technology.DOI: https://dx.doi.org/10.17977/UM014v15i22022p86